Optimization of the power flow of photovoltaic generators in electrical networks by MPPT algorithm and parallel active filters. (November 2021) - Kitmo; Djidimbélé, Répélé; Kidmo, Dieudonné Kaoga; Tchaya, Guy Bertrand; Djongyang, Noël
Abstract: This article presents a method for the reduction of harmonics generated by photovoltaic generators in electrical networks. Very often, photovoltaic generators produce harmonics due to the nature of the direct current they generate. In order to eliminate these harmonics, parallel active filters are used. They are based on seven-level inverters. For the extraction of maximum power produced by the photovoltaic generators, the modified perturb and observe algorithm is used. Furthermore, to reduce the distortions due to the injected continuous quantities, the filtering of the harmonic quantities is done by four levels active filters using three switching cells per arm connected downstream of the seven-level inverters. The proposed algorithm and model of active filter are evaluated, by calculating of the total harmonic distortion of the current before and after filtering. The rate of 0.04 is obtained. Additionally, the simulation results show this rate is lower than that of the standard Institute of Electrical and Electronics Engineers norms. Besides, the voltage and current of the network after the energy injection are in phase.